DOSA KEBIJAKAN PANGAN DI INDONESIA: KAJIAN EKONOMI POLITIK DALAM KEBIJAKAN PUBLIK - Riawanti, Wahyu (Optimum: Jurnal Ekonomi dan Pembangunan, 2012)
This study emphasized in mistakes taken by Indonesian government that explained why food policies have never been in the side of peasents and poor people. The State did not play its role in term of delivering fair food policies for people. It can be seen by the facts that: annual national budget for food and agriculture is relatively small, uneven trade regulation for agriculture products, and unsustainable food policies. It focused in three big sins in food policies which are: trade regulation, political intervention, and institutional conflict of interst. The small design is that imported food related to the givernment good image andÂ  political partiesâ interest. The big design is the everlasting food imports are driven by political party intervention, MNCs interest and international pressure.